1996
DOI: 10.1083/jcb.134.6.1469
|View full text |Cite
|
Sign up to set email alerts
|

Dlg protein is required for junction structure, cell polarity, and proliferation control in Drosophila epithelia.

Abstract: Abstract. The Discs large (Dig) protein of Drosophila is the prototypic member of a growing family of proteins termed membrane-associated guanylate k_inase homologs (MAGUKs). The MAGUKs are composed of a series of peptide domains that include one or three DHR/PDZs, an SH3, and a region homologous to guanylate kinase (GUK). We have previously shown that the product of this gene, the Dig protein, is localized at the septate junctions between epithelial cells, and that mutations in the gene cause neoplastic overg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
404
3
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(418 citation statements)
references
References 59 publications
8
404
3
3
Order By: Relevance
“…The Dlg tumour suppressor is a key regulator of diverse processes including cell polarity control, cell proliferation and cell attachment Woods et al, 1996;Bilder et al, 2000). In addition, recent studies, where exposure to osmotic shock induced an increase in p38g-induced phosphorylation of Dlg (Sabio et al, 2005), have suggested that it may also have a role in the cells' response to changes in the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dlg tumour suppressor is a key regulator of diverse processes including cell polarity control, cell proliferation and cell attachment Woods et al, 1996;Bilder et al, 2000). In addition, recent studies, where exposure to osmotic shock induced an increase in p38g-induced phosphorylation of Dlg (Sabio et al, 2005), have suggested that it may also have a role in the cells' response to changes in the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although all of them appear to be involved in regulating signalling pathways from the cell membrane, most information is available concerning Dlg. In Drosophila, Dlg is classified as a tumour suppressor, regulating processes controlling cell polarity and proliferation (Woods et al, 1996;Bilder et al, 2000). In mice, loss of Dlg function results in craniofacial abnormalities consistent with a breakdown in the normal control of cell polarity (Caruana and Bernstein, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Epithelia form sheets of polarized cells, with the apical and basolateral sides separated by tight junctions (Kim, 1997), and DLG is requried for the organization of these junctional complexes. Tight junctions form a continuous intercellular contact and their absence is associated with defective cell-cell adhesion, a loss of cell polarity and unregulated proliferation (Anderson, 1996;Woods et al, 1996). Maintenance of cell polarity is crucial for normal di erentiation, and the localization of polarity signalling receptors to the basolateral membrane is apparently mediated by PDZ proteins (Woods and Bryant, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…hDlg is expressed in a variety of cell types including epithelia, where it is localized at regions of cell-cell contact (Lue et al, 1994). Interestingly, mutations in Drosophila dlg causes epithelial cells to lose polarity and undergo neoplastic proliferation (Woods et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…De nombreuses études ont démontré le rôle de ces gènes suppresseurs de tumeur dans le contrôle du cycle cellulaire, permettant ainsi d'expliquer la prolifération exacerbée des cellules tumorales. Plus récemment, les gènes suppresseurs de tumeurs ont aussi été impliqués dans le contrôle de la polarité cellulaire [1][2][3][4][5][6][7][8][9][10][11][12]. Parmi ceux-ci, Scribble a initialement été identifié comme gène suppresseur de tumeur chez la drosophile et joue un rôle clé dans la polarité des cellules épithéliales [13].…”
Section: Polarité Cellulaire Et Développement Tumoralunclassified